Uganda : Ex Post Assessment of Performance Under Fund-Supported Programs and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This paper discusses Uganda's Ex Post Assessment of Performance Under IMF-Supported Programs. Uganda's annual average growth rate of about 6 1\2 percent over the past decade was exceptional. Uganda was broadly successful in containing annual inflation to 5 percent during the program period under review. A market-based exchange rate system has provided flexibility in the face of fluctuating coffee prices and large donor inflows. Public expenditure management (PEM) reforms have taken time, but have led to important achievements in the building of budgetary institutions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet